2013
DOI: 10.1007/s00253-013-5431-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a photomixotrophic plant cell culture of Helianthus annuus and optimization of culture conditions for improved α-tocopherol production

Abstract: Tocopherols, collectively known as vitamin E, are lipophilic antioxidants, which are synthesized only by photosynthetic organisms. Due to their enormous potential to protect cells from oxidative damage, tocopherols are used, e.g., as nutraceuticals and additives in pharmaceuticals. The most biologically active form of vitamin E is α-tocopherol. Most tocopherols are currently produced via chemical synthesis. Nevertheless, this always results in a racemic mixture of different and less effective stereoisomers bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 45 publications
3
12
0
2
Order By: Relevance
“…In fact, Martinchik et al (2011) analyzed the nutritional facts of flaxseed and detected that the production of tocopherols was of 92 mg g seed À1 . When comparing these data with our tocopherol values, they are higher those found in flaxseeds and other SCC like sunflower (Geipel et al, 2014), safflower (Furuya et al, 1987) and tobacco (Harish et al, 2013). In fact, Geipel et al (2014) showed that the highest tocopherol levels (77 mg g DW À1 )…”
Section: Effect Of Cyclodextrins Glucan and Hexenol On Tocopherol Prsupporting
confidence: 44%
“…In fact, Martinchik et al (2011) analyzed the nutritional facts of flaxseed and detected that the production of tocopherols was of 92 mg g seed À1 . When comparing these data with our tocopherol values, they are higher those found in flaxseeds and other SCC like sunflower (Geipel et al, 2014), safflower (Furuya et al, 1987) and tobacco (Harish et al, 2013). In fact, Geipel et al (2014) showed that the highest tocopherol levels (77 mg g DW À1 )…”
Section: Effect Of Cyclodextrins Glucan and Hexenol On Tocopherol Prsupporting
confidence: 44%
“…However, these levels of α-tocopherol found were higher than those found in other SCC, e.g., sunflower [52], safflower [53] and tobacco [54]. When Geipel et al [52] characterized the production of α-tocopherol using photomixotrophic and heterorotrophic sunflower SCC, they found that the highest intracellular α-tocopherol levels (77 µg gDW -1 ) were obtained with a photomixotrophic cell culture grown in liquid MS supplemented with 0,5 mg L -1 naphthalene acetic acid, 0,5 mg L -1 benzylaminopurine, 15 g L -1 sucrose and maintained at 26 ºC and a light intensity of 125 µmol m -2 s -1 . Likewise, sunflower and tobacco SCC produced 24 µg gFW -1 and 41 µg gFW -1 of α-tocopherol when 150 µM homogentisic acid alone or in combination with 200 µM phytol was added, respectively [55,54].…”
Section: Effect Of Cds On α-Tocopherol and Chlorophyll Content Of Grementioning
confidence: 48%
“…Moreover, the levels of tocopherols are similar to those found in in other SCC. In fact, photomixotrophic SCC of sunflower were able to produce 77 µg g DW −1 . Likewise, the addition of precursors like homogentisic acid to sunflower SCC enhanced the levels of tocopherol (24 µg g FW −1 ) .…”
Section: Resultsmentioning
confidence: 99%